Nepalese Society in Response to TEVT Programs - Lama, Suman (Himalayan Journal of Sociology and Anthropology, 2017)
Technical education and vocational training programs in Nepalese society have been a aloud offbeat that is combating to slice through the prevalent socio-economic and contemporary social setup so that it could contribute at the very best. Despite more than a half a century’s effort to establish it as a strong element that supports the country’s economy and peoples’ living standard, it has still been straining somewhere near the beginning point. This study investigates some impeding socio-cultural factors that fade the overall development of TEVT programs. The result should help the policy makers to be more assured about the major issues that hurdle the TEVT setup in Nepalese society. Analyzing several research works and national and international reports on concerned topics it is found that the TEVT values have not been placed as one of the top national priorities due to the existing social setup and people’s perspective towards TEVT programs. Therefore the heterogeneous aspects are required to be synchronized even more tactically along with TEVT’s integration in the labor market in order to choreograph, qualitatively improved TEVT programs so that TEVT could be significantly potential element among those on which the country’s socio-economic development could depend on more reliably. Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), page: 155-174